Case Report of Experimental management of Melolontha sp. in a greenhouse strawberry cultivation using biological agents and soil solarization - Karanastasi, Eirini; Κoutroumanis, George; Stavroulias, Dimitrios; Konstantakopoulos , Constantinos (ENTOMOLOGIA HELLENICA, 2023)
The present case report communicates a pilot approach to managing a white grub infestation in a productive, 1-acre (4 stremma), strawberry var. Fortuna greenhouse, where a severe collapse of young seedlings was reported. In this work, the damage caused by Melolontha sp. larvae was monitored for the whole area of the greenhouse (~20,000 plants). Monitoring included detection and recording of the number of affected plants, i.e plants in which a partial or complete absence of the root system upon where the specific larvae were feeding was observed. Other symptoms recorded included smaller plant size, reduced production and complete wilting. A series of non-chemical insecticide formulations (mainly entomopathogenic fungi and entomopathogenic nematodes) were applied alone or in different combinations, in order to test and assess their effectivity against this significant problem. At completion of the cultivation/experimentation period, a 12 ton/acre final production was estimated by the producer, which is considered satisfactory.